2019
DOI: 10.3390/toxins11080441
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Deoxynivalenol Biomarkers in Italian Urine Samples

Abstract: Deoxynivalenol (DON) is a mycotoxin mainly produced by Fusarium graminearum that can contaminate cereals and cereal-based foodstuff. Urinary DON levels can be used as biomarker for exposure assessment purposes. This study assessed urinary DON concentrations in Italian volunteers recruited by age group, namely children, adolescents, adults, and the elderly. In addition, vulnerable groups, namely vegetarians and pregnant women, were included in the study. To determine the urinary DON, its glucuronide and de-epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…It is also of interest to compare DON biomarker levels in this study to data reported in children from some other countries (Table 4 ) . Exposure to DON in Bangladesh is clearly lower than in two regions of China where 10–73% of the cohorts exceed the TDI (Wang et al 2019 ), or in European cohorts: Belgium with 69% above TDI (Heyndrickx et al 2015 ), Italy with 25–27.5% above TDI (De Santis et al 2019 ), Norway with 20% above TDI (Brera et al 2015 ), and the UK, with 33–63% above the TDI (Papageorgiou et al 2018 ). In Africa, children in Cameroon have apparently lower DON exposure (Ediage et al 2013 ) than those in Tanzania geometric mean 2.5 ng/mL, with 21–54% above TDI in one (Srey et al 2014 ) or more in another study (Gong et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also of interest to compare DON biomarker levels in this study to data reported in children from some other countries (Table 4 ) . Exposure to DON in Bangladesh is clearly lower than in two regions of China where 10–73% of the cohorts exceed the TDI (Wang et al 2019 ), or in European cohorts: Belgium with 69% above TDI (Heyndrickx et al 2015 ), Italy with 25–27.5% above TDI (De Santis et al 2019 ), Norway with 20% above TDI (Brera et al 2015 ), and the UK, with 33–63% above the TDI (Papageorgiou et al 2018 ). In Africa, children in Cameroon have apparently lower DON exposure (Ediage et al 2013 ) than those in Tanzania geometric mean 2.5 ng/mL, with 21–54% above TDI in one (Srey et al 2014 ) or more in another study (Gong et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Analyses of urine samples indicated that 40-90% of individuals are exposed to DON. [5,6] Hence, consumer' exposure to DON has become of particular concern, as the TDI may be exceeded in some groups of people. [3,7] The intestine, especially the jejunum, has been identified as the main absorption site of DON, and the first tissue targeted by the toxin.…”
Section: Introductionmentioning
confidence: 99%
“…DON was detected in 76% of urine samples in the Italian population, including children, adolescents, adults, the elderly, vegetarians, and pregnant women, revealing statistically significant differences in population groups, with the highest concentrations of total DON in children and adolescents and the lowest incidence (40–43%) in pregnant women [ 39 ]. On the other hand, conjugation with glucuronic acid was reported as the metabolization route of 80% of DON excreted in urine [ 39 ], and it has been suggested that de-epoxy-deoxynivalenol 1 (DOM-1) is one of the DON detoxifying routes in humans [ 40 ]; therefore, DON metabolites and its conjugation forms should be considered to estimate the total urinary DON by measuring both free and total (free + conjugated) DON before and after enzymatic treatment. The natural occurrence of DON and its metabolites was evaluated in human urine samples from Portugal; 15% of the samples were positive for free DON and 69% were positive for total DON.…”
Section: Resultsmentioning
confidence: 99%